MAPPING AND PROTECTING THE INTELLECTUAL PROPERTY RIGHT IN THE FIELD OF THE TRADITIONAL BATIK DESIGN OF TIRTOMOYO AS THE CULTURAL HERITAGE AND ITS DEVELOPMENT BASED ON THE LOCAL GENIUS IN THE CREATIVE INDRUSTRIAL ERA - Sarwono, Sarwono (Faculty of Law, Universitas Sebelas Maret, 2016)
Abstract In order to provide the protection to the “traditional batik art knowledge” in Tirtomoyo, Wonogiri, the local government policy rests on the potensial of art, commerce, services, education, tourism and sports.Here, it can be drawn the real purpose, that is to develop, to conserve, and to protect the traditional knowledge as the heritage and cultural expression, especially the traditional knowledge. In this case, the Intellectual Property Right protection and its all varieties should be applied on the traditional intellectual art. However, it has not yet manifested the regional regulation on the Intellectual Property Right, especially the protection to the traditional knowledge. There has not been confirmation about what institutions will be responsible or what kind of agencies will be involved in providing the protection to the traditional knowledge, like the batik art, dance art, and others, so that they don’t seem loose accountability in handling it. The policy on the Intellectual Property Right, especially the one related to the traditional knowledge, is still partial or supplement. The Industry and Trade Department of Wonogiri regency, which handles the micro and medium industry field and is not related directly to the batik handicraft industry, has planned to make a program of batik handicraft industry as the regional superior.